The genus Thelypteris (Thelypteridaceae, Polypodiopsida) in the state of Mato Grosso, Brazil, II. Subgenera Amauropelta (Kunze) A.R. Sm., Cyclosorus (Link) C.V. Morton and Steiropteris (C. Chr.) K. Iwats. - Ponce, Marta Monica (2013)
The family Thelypteridaceae presents considerable species richness throughout the hillside forests and coastal plains of Brazil, as well as in the forests of its southern plateau. This study was based on material collected in 24 trips to various regions within the state of Mato Grosso, as well as material deposited in the principal Brazilian herbaria and in other herbaria. The genus Thelypteris, represented in this study by the subgenera Amauropelta (Kunze) A.R. Sm., Cyclosorus (Link) Morton and Steiropteris (C. Chr.) K. Iwats., comprises 11 species in Mato Grosso and surrounding regions. Keys for identification, descriptions and references to illustrations of diagnostic characters are presented.